IMAGING IN DEMENTIA. Issue 12 (15th November 2016) - Bevan-Jones, W Richard; Aigbirhio, Franklin; Passamonti, Luca; Fryer, Tim; Hong, Yong; Coles, Jonathan; O'Brien, John; Rowe, James
Abstract : A 49 year old lady presented with behavioural variant Frontotemporal Dementia in the absence of parkinsonism, supported by neuropsychological testing and frontotemporal atrophy on Magnetic Resonance imaging. Her father had developed behavioural variant Frontotemporal Dementia at 49, with post mortem Tau neuropathology resembling corticobasal degeneration (tau-positive neuronal and glial inclusions, ballooned abnormal achromatic neurons, neuronal loss). His mother had developed dementia in her late 40's. Genetic testing conformed a mutation in the gene MAPT, encoding the microtubule associated protein tau (10+16C>T). Positron Emission Tomography imaging using the novel Tau radioligand [18F]AV-1451 showed increased binding in subcortical grey matter (striatum and thalamus), and cortex. PET radioligands are potentially important biomarkers to detect and monitor tau in many neurodegenerative diseases. In this case, the genetic mutation in the proband and confirmed pathology in her father support the case for [18F]AV-1451 as a biomarker of tau neuropathology. Further work will evaluate the potential for [18F]AV-1451 to monitor presymptomatic mutation carriers; to differentiate tauopathies from other neurodegenerative disorders; and to monitor disease progression and therapy.